Effect of microwave freeze drying on moisture migration and gel characteristics of egg white protein. Issue 9 (15th July 2022) - Liu, Lili; Shi, Shengjuan; Zhang, Yueqi; Li, Yuanyuan; Guo, Jingfang; Zhang, Mengjun
Abstract: This article mainly explored the influence of microwave freeze drying (MFD) power on water migration and gel characteristics of egg white. Fourier transform infrared spectroscopy (FT‐IR), sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE), and scanning electron microscopy (SEM) were used to determine the water migration law and gel characteristics of egg white under different microwave power drying conditions. The results showed that the free water of egg white was removed first, and the water content decreased exponentially at the initial stage of drying. The weakly bound water and bound water accounted for a large proportion, thus, the drying rate decreased in the later stage. SEM showed that the gel strength of egg white protein enhanced with the drying time and reached a maximum of 399.11 g at 5 h. The gel network structure was also denser and smoother than in the initial drying stage. FT‐IR analysis implied that in the early stage of drying, protein molecules were unfolded under the influence of drying conditions, the hydrogen bonds maintaining the α‐helix were broken, and hydrogen bonds content continually decreased. SDS‐PAGE showed that the drying treatment had no effect on the peptide chain structure of the protein, and several protein molecules were gathered at 6 h. This study provides a reference for the MFD of egg white powder. Novelty impact statement: This work shows that microwave freeze drying has a great influence on the characteristics of egg white protein, and drying can improve the network structure of egg white gel, which provides a theoretical reference for the production of high‐quality egg white protein powders.